Efektivitas Penerapan Perawatan Luka Metode Moistwound Healing pada Luka Ulkus Diabetes Militus Tipe II di Rumat Spesialis Luka Diabetes Unit Antapani Bandung - Yunita Sarah Nadeak; Eva Elfrida Pardede (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The prevalence of diabetic ulcers in Indonesia is approximately 15%, with an amputation rate of 30% and a mortality rate of 32%. Diabetic ulcers account for 80% of hospitalizations among Diabetes Mellitus patients, due to a combination of peripheral neuropathy and ischemia. The Moist Wound Healing (MWH) method is used to accelerate the healing of diabetic ulcers. MWH maintains wound moisture, creating an optimal environment for tissue growth, speeding up healing, and reducing the risk of infection. This study used a quasi-experimental approach with a pre-test and post-test design, involving 15 patients at the Diabetic Wound Specialist Clinic, Antapani Unit, Bandung. Wound care was carried out over 21 days with weekly observations. Data were analyzed using the Wilcoxon test. The results showed a significant improvement in wound condition after MWH treatment. Before treatment, 40% of patients were in the inflammatory phase, and 60% in the proliferative phase. After treatment, 66.7% were in the proliferative phase, and 20% had reached the remodeling phase. The Wilcoxon test showed a p-value of < 0.001, indicating a significant difference before and after treatment. Conclusion: MWH is effective in accelerating diabetic ulcer healing by promoting the proliferative and remodeling phases. Recommendation: Future studies may explore other factors affecting healing and compare MWH with other wound care method